O16.4 Structural similarity of treponema pallidum protein Tp0225 with human toll-like receptor 2. (14th July 2019) - Houston, Simon; Ramaswamy, Raghavendran; Loveless, Bianca; Boulanger, Martin; Cameron, Caroline
Abstract : Background: The causative agent of syphilis, Treponema pallidum, is a highly invasive chronic pathogen. Here we used bioinformatics and structural biology to characterize the sole LRR-containing protein in T. pallidum, Tp0225. In other bacterial pathogens, Leucine-Rich Repeat (LRR)-containing proteins contribute to chronicity by mediating attachment, invasion and immune evasion. Methods: A phylogenetic tree was constructed to determine the evolutionary relationship between Tp0225 and LRR homologs from pathogenic and non-pathogenic treponemes. The size and organization of Tp0225 protein domains were analyzed by comparing them to the domains of the treponemal homologs. For structure determination, the full-length recombinant protein was purified, crystallized, and the three dimensional structure determined using X-ray crystallography. Results: Bioinformatic analyses showed that Tp0225 has diverged more from non-pathogens compared to pathogens during evolution. The structure of Tp0225 demonstrated that the protein adopts a non-classical LRR fold and contains a hydrophobic pocket on the surface of the structure. This unusual LRR characteristic is similar to the hydrophobic pocket found on the surface of the human Toll-like Receptor 2 (TLR2) LRR domain that recognizes T. pallidum during infection. Conclusion: We have determined the structure of the only LRR-containing protein in T. pallidum and have shown that it contains an unusual LRR structural feature that is shared with the host innate immune signaling molecule TLR2. This structural mimicry may be involved in subversion of normal host processes during T. pallidum infection. Disclosure: No significant relationships.